Did the Wisconsin Supreme Court Restart a COVID-19 Epidemic? Evidence from a Natural Experiment - Dhaval M. Dave; Andrew I. Friedson; Kyutaro Matsuzawa; Drew McNichols; Joseph J. Sabia (Institute of Labor Economics (IZA), 2020)
Both the White House and state governors have explicitly linked thresholds of reduced COVID-19 case growth to the lifting of statewide shelter-in-place orders (SIPOs). This "hardwired" policy endogeneity creates empirical challenges in credibly isolating the causal effect of lifting a statewide SIPO on COVID-19-related health. To break this simultaneity problem, the current study exploits a unique natural experiment generated by a Wisconsin Supreme Court decision. On May 13, 2020, the Wisconsin Supreme Court abolished the state's "Safer at Home" order, ruling that the Wisconsin Department of Health Services unconstitutionally usurped legislative authority to review COVID-19 regulations. We capitalize on this sudden, dramatic, and largely unanticipated termination of a statewide SIPO to estimate its effect on social distancing and COVID-19 case growth. Using a synthetic control design, we find no evidence that the repeal of the state SIPO impacted social distancing, COVID-19 cases, or COVID-19-related mortality during the fortnight following enactment. Estimated effects were economically small and nowhere near statistically different from zero. We conclude that the impact of shelter-in-place orders is likely not symmetric across enactment and lifting of the orders.
Keywords: H75; I18; 330; coronavirus; COVID-19; shelter-in-place order; synthetic control